Radicalization from a societal perspective - Shafieioun, Delaram; Haq, Hina (Frontiers in Psychology, 2023)
Studies on radicalization tend to focus on the dynamics of extremist groups and how they exploit grievances of vulnerable individuals. It is imperative, however, to also understand the societal factors that lead to such vulnerabilities and grievances. Our social environment plays a key role in how we view the world and shape our beliefs. By understanding the social dynamics, we can gain insight into the motivations that drive people to extremism. Throughout this paper, we examine the societal factors and processes such as discriminative institutional structures and social norms/practices that can make an individual vulnerable and serve as a driving force for them to join a radical group. To do that, we use the process-oriented psychology of Arnold Mindell and the phenomenology of whiteness of Sara Ahmed as our theoretical framework. These frameworks help us map out the societal dynamics causing individuals to carve social niches out of their current social group and into an extremist group. We use interviews with ex-militants of the radical group, Islamic State of Iraq and Syria, to show how certain societal dynamics, such as social injustice, misuse of power, marginalization and discrimination, served as key factors that led these individuals to identify and sympathize with radical ideology. The aim of this paper is to emphasize that, to develop effective preventative measures against recruitment into extremist groups, it is imperative to have a profound understanding of the social dynamics that make an individual susceptible to radicalization in the first place.